[OP.2A.04] COMPARISON OF CAROTID-FEMORAL AND BRACHIAL-ANKLE PULSE WAVE VELOCITY IN THE ASSOCIATION WITH TARGET ORGAN DAMAGES IN THE COMMUNITY-DWELLING ELDERLY: THE NORTHERN SHANGHAI STUDY. (September 2016) - Lyu, Y.; Bai, B.; Chi, C.; Yu, S.; Wang, K.; Xiong, J.; Zhang, Y.; Xu, Y.
Abstract : Objective: To compare of carotid-femoral pulse wave velocity (cf-PWV) and brachial-ankle PWV (ba-PWV) in the association with conventional cardiovascular risk factors and target organ damages (TODs). Figure. No caption available. Design and method: 1599 community-dwelling elderly subjects (age>65 years old) in the northern Shanghai were recruited from June 2014 to August 2015. Cf-PWV and ba-PWV were measured by SphygmCor (AtCor, Australia) and VP1000 (Omron, Japan), respectively. Under the framework of comprehensive cardiovascular examinations, cardiovascular risk factors were assessed, and hypertensive TODs, including left ventricular mass index (LVMI), peak transmitral pulsed Doppler velocity/early diastolic tissue Doppler velocity (E/Ea), carotid intima-media thickness (CIMT), ankle-brachial index (ABI), creatinine clearance rate (CCR) and urinary albumin-creatinine ratio (UACR), were all evaluated. Results: Both cf-PWV and ba-PWV were significantly associated with gender, age, waist / hip circumference, fasting plasma glucose and systolic blood pressure, and ba-PWV was also significantly related with body mass index. Both cf-PWV and ba-PWV were significantly correlated with most TODs, but cf-PWV was more predictable than ba-PWV for ABI (r = −0.17 vs r = −0.06, p < 0.05) and CCR (r = −0.15 vs r = −0.05, p < 0.05). After adjustment for confounders, cf-PWV was significantly associated with CIMT (6.2 ± 1.9 um, p = 0.001), ABI (−0.005 ± 0.001, p = 0.001), CCR (−0.63 ± 0.29 ml/min/1.73 m2, p = 0.030), and UACR (5.8 ± 2.6, p = 0.02), but not ba-PWV. When both cf-PWV and ba-PWV were put into the same model, cf-PWV were also significantly correlated with CIMT, ABI, and CCR, but not ba-PWV. Similar results were observed in logistic regression analysis. Conclusions: In the community-dwelling elderly, cf-PWV was more closely associated with hypertensive TODs, especially vascular and renal TODs, as compared with ba-PWV.